2014
DOI: 10.1371/journal.pone.0115278
|View full text |Cite|
|
Sign up to set email alerts
|

DNA Methylation Analysis of the Macrosatellite Repeat Associated with FSHD Muscular Dystrophy at Single Nucleotide Level

Abstract: Facioscapulohumeral muscular dystrophy (FSHD) is one of the most common inherited diseases of the skeletal muscle. It is characterized by asymmetric muscle weakness and variable penetrance. FSHD is linked to a reduction in copy number of the D4Z4 3.3 kb macrosatellite repeat, located in 4q35. This causes the epigenetic de-repression of FSHD candidate genes leading to disease. Nevertheless, the molecular mechanism responsible for silencing of FSHD candidate genes in healthy subjects is not fully understood. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 59 publications
3
38
0
Order By: Relevance
“…FSHD1, which accounts for 95% of FSHD cases, is an autosomal dominant disease caused mainly by a DNA contraction of the D4Z4 macrosatellite repeat elements found on human chromosome 4, specifically 4q35 (8,11,12). This D4Z4 repeat reduction results in epigenetic changes at the locus, such as DNA hypomethylation within the D4Z4 repeats and the surrounding locus (13)(14)(15) as well as the loss of repressive histone methyl marks (16). It was postulated that the change in chromosomal conformation from heterochromatin to euchromatin facilitates access to DUX4 by as of yet unidentified transcriptional activators.…”
mentioning
confidence: 99%
“…FSHD1, which accounts for 95% of FSHD cases, is an autosomal dominant disease caused mainly by a DNA contraction of the D4Z4 macrosatellite repeat elements found on human chromosome 4, specifically 4q35 (8,11,12). This D4Z4 repeat reduction results in epigenetic changes at the locus, such as DNA hypomethylation within the D4Z4 repeats and the surrounding locus (13)(14)(15) as well as the loss of repressive histone methyl marks (16). It was postulated that the change in chromosomal conformation from heterochromatin to euchromatin facilitates access to DUX4 by as of yet unidentified transcriptional activators.…”
mentioning
confidence: 99%
“…It is noteworthy that YY1 binds DNA only when it is not methylated [105]. The region encompassing the DBE element is hypermethylated in FSHD and control subjects, except from the CpGs neighboring the YY1 consensus site, which show variable levels of methylation (Tupler, personal observation and [106]). Conversely, CTCF binding is disrupted by CpG methylation [107].…”
Section: Trans-acting Factorsmentioning
confidence: 99%
“…Conversely, CTCF binding is disrupted by CpG methylation [107]. Two CTCF binding sites are located within the 5 region of D4Z4 repeat, which is reported to display hypomethylation in the presence of a DRA [74,101,106,108]. CTCF binding to 4q35 displays an inverse correlation to D4Z4 copy number and function as a Lamin A/C-dependent chromatin insulator, protecting D4Z4 from epigenetic silencing by surrounding heterochromatic regions, therefore keeping the D4Z4 chromatin open primarily in a DRA context [102].…”
Section: Trans-acting Factorsmentioning
confidence: 99%
“…Commonly, healthy individuals carry an array of more than 10 repeats. However, even long arrays result in FSHD symptoms when losing their methylation (termed FSHD2) while carriers of short but highly methylated repeat arrays, do not manifest the disease 15,16 . The multiple combinations of copy number and methylation level span a broad range of possible variations which are correlated with the disease severity and manifestation 16,17 .…”
Section: Simultaneous Quantification Of Copy Number and Methylation Smentioning
confidence: 99%
“…In this context, it has been shown that methylation levels of repetitive DNA can regulate repeat-related genetic diseases 12,13 , and are correlated with various types of cancer and their severity 14 . One striking example of a repeat array, addressed in this work, is facioscapulohumeral muscular dystrophy (FSHD), one of the most commons form of muscular dystrophy, affecting approximately 1 in 7,000-20,000 individuals [15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%